Simultaneous positron emission tomography and magnetic resonance image reconstruction with compressive sensing using cross-prior information and pre-filtering - Silva, Gabriela Barbosa (2025)
Dissertação (Mestrado em Engenharia Biomédica) — Universidade de Brasília, Faculdade UnB Gama, Programa de pós-graduação em Engenharia Biomédica, 2025.